Exploring Oroxylum indicum Phytochemicals as VEGFR-2 Inhibitors: A Molecular Docking Approach for Cancer Management - N.G. Prathikshaa (International Journal of Cell Biology and Cellular Functions, 2025)
Cancer is still a major health problem around the world and is one of the top causes of death. A protein called VEGFR-2 (vascular endothelial growth factor receptor 2) is important because it helps blood vessels grow by supporting the survival, movement, and growth of certain cells. This process is essential for tumors to grow and spread to other parts of the body. This study focused on evaluating the binding energy of phytochemicals from Oroxylum indicum with VEGFR-2 using computational techniques. Molecular docking was conducted via PyRx, a virtual screening tool, to analyze ligand-protein interactions. The data and molecular structures of the plant-based compounds and target proteins were obtained from databases like IMPPAT (Indian Medicinal Plants, Phytochemistry and Therapeutics) and PubChem. Protein structure validation was performed using tools, such as Protein Data Bank (PDB) Sum and BIOVIA Discovery Studio. The pharmacological properties of the ligands were assessed using ADME filters to determine their drug-like characteristics and therapeutic viability. Docking results identified Apigenin 7,4'-dimethyl ether, Biochanin A, Chrysin, Flavone (5,7-dihydroxy-6-methoxy), Hispidulin, Oroxylin A, and Prunetin, as ligands with the lowest binding energies to VEGFR-2. These plant-based compounds show promise as effective blockers of growth factor receptors, which are known to play a key role in the development and spread of cancer. While these findings suggest their suitability as candidates for cancer treatment and suppression, further in vitro investigations are essential to confirm their efficacy.
Keywords: Oroxylum indicum; Phytochemicals; VEGFR-2 inhibition; cancer therapeutics; molecular docking; tumor angiogenesis